Comparisons Of Restored Blurred-Noisy Dental Images Using Wiener Filter And Lucy-Richardson Technique. (International Journal of Engineering and Computer Science, 2015)
This paper   attempts to    compare  dental    images (grayscale/truecolor) degraded with blur and noise using  different de-blurring   filters. The   image   is degraded by the combination of Gaussian/Average blur and   Salt & Pepper /Speckle / Poisson  /  Gaussian  noise   for different values   of   PSF.  All   the   degraded images are  then restored using Wiener Filter, Lucy Richardson Filter technique. Restoration by Wiener filter takes place for different values of estimated NSR and restoration by Lucy-Richardson for different iterations.  The  restored  images  are    then  compared on the basis of SNR, MSE and PSNR values.This   comparison   are  made to  find which   filter technique removes which  combination of blur and noise on what value of PSF with  high PSNR/SNR and low MSE value.